ANALISIS KEMAMPUAN LITERASI MATEMATIS SISWA SMP DI KOTA CILEGON - Putri, Risma Nandini; Pujiastuti, Heni; Yuhana, Yuyu (LPPM Universitas Bina Bangsa, 2024)
Mathematical literacy skills are students' ability to analyze mathematical problems. Based on the results of PISA (Program for International Student Assessment), the level of mathematical literacy of students in Indonesia is still low. One way to find out the level of students' mathematical literacy skills is to provide description test questions. In this study, researchers will provide mathematical literacy description test questions which are limited to five of the six PISA levels of mathematical literacy. This test will cover three main indicators of mathematical literacy, namely formulating, using concepts, facts and mathematical reasoning (employ), and interpreting and evaluating (interpret). This research aims to analyze the mathematical literacy abilities of junior high school students in Cilegon City. The method used in this research is Systematic Literature Review (SLR). The analysis was carried out by collecting data from articles and journals that were relevant to the topic of discussion, namely the mathematical literacy abilities of junior high school students.